2005
DOI: 10.1103/physrevb.71.024112
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced rotation of spontaneous polarization in monoclinic and triclinicPbZr0.52Ti0.48O3

Abstract: The morphotropic composition of lead zirconate titanate ͑PZT͒, PbZr 0.52 Ti 0.48 O 3 , was studied as a function of temperature ͑47-310 K͒ and hydrostatic pressure ͑from 0.1 MPa to 7.6 GPa͒ by neutron powder diffraction. Series of monoclinic ͑space groups Cm and Cc͒ and triclinic phases ͑space groups F1 and F1͒ were observed at various points in the P-T phase diagram of PbZr 0.52 Ti 0.48 O 3 . The high-pressure behavior is characterized by two mechanisms, a rotation and reduction of the spontaneous polarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 47 publications
(52 reference statements)
10
58
0
Order By: Relevance
“…This discovery of AFD transition below room temperature was subsequently confirmed by several workers [7][8][9][10][11][12][13] .…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…This discovery of AFD transition below room temperature was subsequently confirmed by several workers [7][8][9][10][11][12][13] .…”
Section: Introductionsupporting
confidence: 53%
“…The space group of this monoclinic phase was first shown by Hatch et al 18 to be Cc which was subsequently confirmed by others [11][12][13] but an alternative model based on the coexistence of R3c+Cm phases has also been proposed by some workers 8,9 .…”
Section: Introductionmentioning
confidence: 66%
“…Ref. [31][32][33]). However, the most striking observation was that the model ferroelectric and simple perovskite PbTiO 3 first reduces its ferroelectricity and becomes cubic but then, unlike commonly thought, becomes again non-cubic with tetragonal phases [12,34,35] through mechanisms involving oxygen octahedra tilting [12] and a theoretically predicted re-entrance of ferroelectricity [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…From lead zirconate [55][56][57][58] to lead titanate [59][60][61][62][63] through several intermediate compositions [64][65][66][67][68], PZT has been studied under pressure. Among the numerous interesting results in this field, a high-pressure form of ferroelectricity has been calculated and observed in PbTiO 3 [59,60] at room temperature.…”
Section: D and 3d Stress Fieldsmentioning
confidence: 99%